2022
DOI: 10.1016/j.arcped.2022.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Distress, anxiety, and its correlates among caregivers of children with kidney diseases during COVID-19 pandemic lockdown

Abstract: Background : The COVID-19 pandemic has generated a significant amount of psychological burden in the form of stress, anxiety, uncertainty, depression, anger, and helplessness. The caregivers of children with chronic diseases in particular are at a higher risk of mental stress and burden. Material and Methods : We conducted an online survey among caregivers of children with kidney diseases to assess the psychosocial impact of COVID-19. The psychosocial impact of COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…During the pandemic, this often-unseen care burden has been experienced disproportionately by families struggling with adverse social determinants of health and health disparities. Caregivers of children with kidney disease reported feelings of stress, anxiety, depression and insomnia during the pandemic, mirroring findings in parents of children with other chronic conditions 117 , 118 . Children with medical complexities have lost access to therapies, educational services and peer interactions, all while parents and caregivers have taken on additional responsibilities to navigate changes in employment and keeping their families healthy 119 .…”
Section: Psychosocial Aspects Of Covid-19mentioning
confidence: 53%
“…During the pandemic, this often-unseen care burden has been experienced disproportionately by families struggling with adverse social determinants of health and health disparities. Caregivers of children with kidney disease reported feelings of stress, anxiety, depression and insomnia during the pandemic, mirroring findings in parents of children with other chronic conditions 117 , 118 . Children with medical complexities have lost access to therapies, educational services and peer interactions, all while parents and caregivers have taken on additional responsibilities to navigate changes in employment and keeping their families healthy 119 .…”
Section: Psychosocial Aspects Of Covid-19mentioning
confidence: 53%
“…COVID-19-related financial distress and work impairment were also associated with higher symptom levels of depression ( 48 ). A recent study ( 49 ) showed that 78.5% of caregivers of children with kidney diseases reported depressive symptoms during the pandemic, which was 32.8–48.3% higher than those in previous studies ( 50 , 51 ). Meanwhile, the incidence of subjective depressive symptoms increased from 5.9 to 60% among caregivers of patients with dementia ( 52 ).…”
Section: Discussionmentioning
confidence: 71%
“…Ainda diante da evidência trazida através do estudo (21) , a respeito da hemodiálise, a pesquisa (23) Em concordância com os dados apresentados anteriormente, o estudo (26) investigou que a grande maioria dos pacientes Em contradição aos estudos trazidos nesse tópico, a pesquisa (18) realizou uma análise…”
Section: De Acordo Com As Informações Do Estudounclassified